Assessment of Pest and Pesticide Trends in Vegetable Crops in the United Arab Emirates and Sultanate of Oman - Talukdcr, F. A.; Kaakeh, W; ldahmani, J. H . A; Maraqa, M .; Deadman, M. L.; Jabri, S. A. A I-; Saadi, A. A l-; Raecsi, A. A . A l-; Hasani, H. Al; Subhi, L. A l-; Ilosamrah, A . A. (Biological Sciences - PJSIR, 2007)
. A prelim i n ary survey on pesti cid e uses i n 40 vegetable-grow i ng farms represen t i n g di fferen t agricu l tu ra l areas i n Om an an d th e U A E, twenty farm s from each coun try, revealed th a t a l l th e vegetab l e farm s u sed pesti cides for crop protection . A mon g th e major i n sect-pests, w h i t cflies ( Bemisia tabaci) , l eafmin ers ( Li riomyza tr/ f o/i i) , mel on fru i t fli es ( Bactrocera cilia/us) , aph i ds ( Ap lz is spp . ) an d tobacco l eafworm (Spodoptera / iueralis) w ere recorded i n Oman i fa rm s. I n t he UAE, whiteflies, J eafm i n crs, cu tworm s ( Agrotis yp sila 11), tomato fru itworm s ( He/icoverp a armigera) u n d eggpl an t fru i twom,s ( Leucinodes orbonalis) w ere t h e 5 top i n sect-pests. A mon g th e p l ant diseases, powdery m i l dew ( Erys ip he spp.), bl i ght ( Al lemaria spp.), dam p i n g off (Py thium spp.), J cafspot ( A /t ernaria spp . ) and m osai c ( CMV ) were m aj or cau se of vegetabl e d i seases i n Oman i farm s; w h ereas, dam pi n g off (Py thium ap / ,a n idermatum), down y mi ldew ( Pseudop eronsp ora cubensis), earl y bl i ght (Alt ernaria solani ), sept ori a l eaf spot ( Septo ria lycopersic:i) and anth racn ose ri p rot ( Co/l etotrichum spp.) were th e m ost pred om i n an t di seases encountered i n most U A E farm s. A m ong th e m ost comm onl y u sed pesti cid es, 29 i n sect i c i des, 16 fu n gi cides an d 3 h e 1·bi c i des w ere u sed by t h e veget abl e fa rm ers. A roun d 55% of Om an i farms u sed rou ti n e app l i cat ion of pesti cid es, i rrespect i ve of th e pest presen ce. Wh ereas, i n th e UAE , most farmers started to spray pesticides at 6-20% pest (i n sect , di sease & w eed s) i n festa t i on . Over 65°1., of t h e farm s, i n both the countries, recei ved chemical pest man agem ent i nform ation from the sales represen tat i ves.